Antiproliferative and proapoptotic activity of Turkish propolis on human lung cancer cell line. (2nd January 2016) - Demir, Selim; Aliyazicioglu, Yuksel; Turan, Ibrahim; Misir, Sema; Mentese, Ahmet; Yaman, Serap Ozer; Akbulut, Kubra; Kilinc, Kagan; Deger, Orhan
Abstract: Cancer is a heterogeneous disease, two of whose characteristic features are uncontrollable cell proliferation and insufficient apoptosis. Various studies have investigated the antiproliferative effects of propolis, a natural bee product, from different countries, and its cytotoxic effects have been attributed to its polyphenol contents. The purpose of this study was to show the cytotoxic effects, and possible mechanisms involved, of ethanolic extract of Turkish propolis (EEP) on the human lung cancer (A549) cell line. Cytotoxic activity of EEP on A549 cells was revealed using the MTT assay. Mechanisms involved in the cytotoxic action of EEP on A549 cells were then investigated in terms of apoptosis, mitochondrial membrane potential and cell cycle using flow cytometry, endoplasmic reticulum stress using RT-PCR, and caspase activity using luminometric analysis. EEP exhibited selective toxicity against A549 cells compared to normal fibroblast cells. We determined that EEP arrested the cell cycle of A549 cells at the G1 phase, induced endoplasmic reticulum stress, caspase activity, and apoptosis and reduced mitochondrial membrane potential. These results indicate that Turkish propolis is capable of reducing cancer cell proliferation and may have a promising role to play in the development of new anticancer drugs in the future.